ChemInform Abstract: Stereoselective Synthesis of C19—C27 Fragment of Bryostatin 11. Issue 2 (January 2015) - Yadav, J. S.; Swamy, T.; Subba Reddy, B. V.; Ravinder, V.
Abstract The key steps for the synthesis of the title fragment (I) are kinetic resolution, Grignard reaction, Sharpless dihydroxylation, and for the first time, AIBN radical cyclization to construct the six‐membered pyran system.